Dokazi o učinkovitosti terapije z laserjem - Kos, Nataša (Rehabilitacija (Ljubljana), 2011)
The first publication about low level laser therapy (LLLT) appeared 40 years ago in Hungary. Since then, large numbers of studies demonstrating results of LLLT in cells in vitro, animal models and clinical reports have been published, but the results remains controversial. Some studies found positive effects, but many negative studies have also been published. Nevertheless, the use of LLLT has become widespread by physical therapists and usually the effects are positive. There is a need for further methodologically rigorous randomised controlled studies to evaluate the effects of LLLT compared to other treatments, different lengths of treatment, wavelengths and dosages.
Keywords: biostimulacija; bolečina; celjenje ran; therapy; zdravljenje